Mental Health Service in Ghana: A Review of the Case - Samuel Adu-Gyamfi (International Journal of Public Health Science (IJPHS), 2017)
Mental health care in Ghana has been fraught with several challenges leading to stagnant growth in mental health service delivery and in some cases a severe depreciation in the nature of care. The Government of Ghana pays little or no attention to mental health care in the country, a situation that has led to poor service delivery in the three major psychiatric hospitals in Ghana. The implementation of the Ghana Mental Act of 2012 has also been faced with major challenges with no significant progress being made. This studytherefore sought to review and document the development of mental health care services in Ghana. Specifically, the study examined the various legislations on mental health that have been enacted  in Ghana since 1900; investigated the implementation of the current Mental Health Act of Ghana; found out whether the Ghanaian government has prioritise mental health services in the country and assessed the challenges and problems that confronted mental health services in Ghana since 1900.The study concludes that, since 1888 efforts have been made by various governments to legislate the provision of mental services in Ghana. However, these legislations have not always protected the rights and interest of the mentally ill.